(3EOGQI GdCOGA HESJNOGe HWGbI GdCOGA GdeJhGRf (B/s - (3GdedcGhj, EHQGgje GdNdhas ((3YeGf(B: s (3eDSSI GdhQGb ddfTQ(B, s, 2008)
(3HWGbI GdCOGA GdeJhGRf,GdefXhQ GdeGdj,efXhQ GdYedGA,eMhQ GdYedjGJ,eMhQ GdJYde hGdfeh,QHW HWGbI GdCOGA HGdESJQGJjLjI,cjajI JWhjQ HWGbI GdCOGA GdeJhGRf,MGdI YedjI Mhd JUeje hJWHjb HWGbGJ GdCOGA GdeJhGRfs
(3HHdjhZQGajG(B:(3U U(B.255-256s
Keywords: (3GdEOGQIs